PENGARUH PEMBERIAN â€™â€™PUYER HERBALâ€ TERHADAP BOBOT PANEN, NEKROSIS USUS HALUS, DAN pH USUS HALUS PADA AYAM BROILER - Ceunfin, Sisilia; Supartini, Nonok; Thiasari, Nurita (Universitas Tribhuwana Tunggadewi, 2018)
The purpose of this study was to determine the effect of different levels of herbs powder to the on slaughter weight, intestinal necrosis, and pH Intestine in broiler chickens, as well as to obtain ideal herbs powder level for broiler chickens. The feed used BR1 for 1-7 days old and feed formulations for 8-35 days old consist of: yellow corn, pollard, meat meal, soybean meal, salt, DL-Metionin and lysine. Method P0 : feed formulation without herbs powder, P1 : feed formulation + 0.3% herbs powder, P2: feed formulation + 0.6% herbs powder, P3 : feed formulation + 0.9% herbs powder. The herbs powder administration based on weekly body weight. This research method used Completely Random Design with 4 treatments and 4 replications. The results showed that the administration of herbs powder with different levels significantly affected (P